Paricalcitol Inhibits Wnt/?-Catenin Signaling Pathway and Ameliorates Dermal Fibrosis in Bleomycin Induced Scleroderma Model - Gozel, Nevzat; Duran, Fikret; Yildirim, Ahmet; Yolbas, Servet; Onalan, Ebru; Ozercan, Ibrahim Hanifi; Koca, Suleyman Serdar (Turkish League Against Rheumatism, 2018)
Objectives: This study aims to determine the prophylactic and therapeutic efficacy of inhibition of Wnt/beta-catenin signaling pathway with paricalcitol in an experimental scleroderma model created with bleomycin (BLM). Materials and methods: Sixty female BALB/c mice (8-week old and weighing 25 g to 30 g) were divided into six groups as prophylactic-early [control I (group 1)1, sham I (group 2), paricalcitol I (group 3), therapeutic-late [control II (group 4)1, sham II (group 5), and paricalcitol II (group 6) groups. Subcutaneous BLM (100 mu g/day) injections were used to induce dermal fibrosis and paricalcitol (0.3 mu g/kg/day) was applied subcutaneously to BLM-injected mice during the first three weeks for preventive interventions and in the second three weeks for therapeutic interventions. Tissue samples were harvested for subsequent pathological and real-time polymerase chain reaction (RT-PCR) analysis. Tissue transforming growth factor-beta 1 (TGF-beta 1), axin-1, and Wnt-2 messenger ribonucleic acid (mRNA) expressions were determined by RT-PCR. Results: Repeated BLM applications increased the dermal inflammatory cell infiltration and dermal thickness, and led to dermal fibrosis, in both early and late stages. Similarly, TGF-beta 1, axin-1, and Wnt-2 expressions were significantly increased in the sham groups compared to the own control group (p<0.05 for all). Contrarily, prophylactic and therapeutic paricalcitol applications decreased the TGF-beta 1, axin-1, and Wnt-2 mRNA expressions compared to the own sham group (p<0.05 for all). In addition, the regressions in dermal necro-inflammation and dermal fibrosis on pathological views were also observed in the paricalcitol applied groups. Conclusion: In this model, increased axin-1 and Wnt-2 mRNA expressions suggest that Wnt/beta-catenin pathway is active in dermal fibrosis.
Keywords: Dermal fibrosis; paricalcitol; scleroderma; Wnt/beta-catenin pathway